Asymmetric total synthesis of L-allo-1-deoxynojirimycin - Chavan, Subhash P.; Dumare, Nilesh B.; Pawar, Kailash P.; Chavan, Prakash N.; Khairnar, Lalit B. (Arkivoc, 2016)
Asymmetric total synthesis of L-allo-1-deoxynojirimycin (L-allo-DNJ) was achieved from cis-butene-1,4-diol by employing Sharpless asymmetric dihydroxylation, stereoselective flash dihydroxylation and ring enlargement reactions as key steps.
Keywords: diastereoselective flash dihydroxylation; ring-enlargement reaction; sharpless asymmetric dihydroxylation